2013
DOI: 10.1007/s00343-013-2124-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of salinity on toxicological effects of arsenic in digestive gland of clam Ruditapes philippinarum using metabolomics

Abstract: Ruditapes philippinarum , a clam that thrives in intertidal zones of various salinities, is a useful biomonitor to marine contaminants. We investigated the infl uence of dilution to 75% and 50% of normal seawater salinity (31.1) on the responses of the digestive gland of R . philippinarum to arsenic exposure (20 μg/L), using nuclear magnetic resonance (NMR)-based metabolomics. After acute arsenic exposure for 48 h, salinity-dependent differential metabolic responses were detected. In normal seawater, arsenic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…A) . Membrane phospholipids are important targets of free radicals action, resulting in lipid peroxidation that leads to the loss of membrane integrity and function, which has been demonstrated by other authors . This observation is corroborated by the altered levels of free fatty acids (Table ), such as arachidonic acid and docosahexaenoic acid detected by ESI‐ analysis in the polar extract.…”
Section: Resultssupporting
confidence: 58%
“…A) . Membrane phospholipids are important targets of free radicals action, resulting in lipid peroxidation that leads to the loss of membrane integrity and function, which has been demonstrated by other authors . This observation is corroborated by the altered levels of free fatty acids (Table ), such as arachidonic acid and docosahexaenoic acid detected by ESI‐ analysis in the polar extract.…”
Section: Resultssupporting
confidence: 58%
“…Alteration of ATP/ADP levels, along with arginine, has been reported in marine mollusks in response to different types of stress (Jones et al, 2008;Spann et al, 2011;Viant et al, 2003;Liu et al, 2011). Furthermore, metabolomics studies revealed that glycine content is related to the health states of oysters and clams, with reductions of this amino acid occurring after infection with pathogens (Liu et al, 2013), exposure to heavy metals (Ji et al, 2013), and under hypo-osmotic conditions (Meng et al, 2013).…”
Section: Metabolic Responses In the Digestive Glandsmentioning
confidence: 99%
“…This result was consistent with the role of glycine as a common osmolyte in marine bivalves 44 , 46 . Previous studies revealed that glycine content was related to the health state of oysters and clams, with reductions in this amino acid occurring after infection with pathogens 47 , after exposure to heavy metals 48 , and under hypo-osmotic conditions 49 . Young et al also demonstrated that glycine content is significantly reduced in poor-quality cohorts 50 .…”
Section: Discussionmentioning
confidence: 99%